2007
DOI: 10.1097/mlg.0b013e31804154b1
|View full text |Cite
|
Sign up to set email alerts
|

Failures of Adenoidectomy for Chronic Rhinosinusitis in Children: For Whom and When Do They Fail?

Abstract: Those who fail adenoidectomy for CRS who require ESS are mainly children who are younger than 7 years of age and have asthma. They appear to require a salvage ESS at a mean of 24 months after the adenoidectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 13 publications
3
32
0
Order By: Relevance
“…Ramadan et al [25] reported that adenoidectomy was effective in 50% of pediatric sinusitis patients and Vandenberg et al [3] reported that it was effective in 79% of pediatric sinusitis patients. Clary [29] and Lieser et al [30] also considered adenoidectomy as the first surgical choice for pediatric sinusitis patients unresponsive to medical therapy.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Ramadan et al [25] reported that adenoidectomy was effective in 50% of pediatric sinusitis patients and Vandenberg et al [3] reported that it was effective in 79% of pediatric sinusitis patients. Clary [29] and Lieser et al [30] also considered adenoidectomy as the first surgical choice for pediatric sinusitis patients unresponsive to medical therapy.…”
Section: Discussionmentioning
confidence: 98%
“…Adenoid hypertrophy may mimic sinusitis symptoms by causing obstruction and stasis of secretions. This stasis of secretion may in turn obstruct sinus ostium and cause sinusitis [25]. Although adenoid hypertrophy can cause mechanical obstruction, more reports show that adenoid volume has little correlation with sinusitis.…”
Section: Discussionmentioning
confidence: 99%
“…Subgroup analysis by age of subject, follow-up time, and adenoidectomy technique (curette versus cautery) was planned a priori but the small sample size and similar age and follow-up time precluded this type of analysis. Given three of the ten articles were published by the same author(s) [7,10,11], there was concern for a possible author bias that could have effected the results. The studies by Ramadan et al each reported a success rate for adenoidectomy that was considerably lower than most of the other studies.…”
Section: Resultsmentioning
confidence: 98%
“…Application of the inclusion criteria initially resulted in only six articles meeting the inclusion criteria. Hand searching of the references resulted in an additional three articles for a total of nine studies [3][4][5][6][7][8][9][10][11]. Table 1 is the evidence table that summarizes the general findings of the selected articles.…”
Section: Resultsmentioning
confidence: 99%
“…Adenoidectomy alone is widely accepted as a first surgical procedure in pediatric patients with CRS, but studies suggest that only 50-60% of patients will have long term improvement [5]. These refractory cases leave the surgeon few options before proceeding to FESS.…”
Section: Discussionmentioning
confidence: 95%